A review of metallic nanoparticles: present issues and prospects focused on the preparation methods, characterization techniques, and their theranostic applications - Shahalaei, Mona; Azad, Abul Kalam; Sulaiman, Wan Mohd Azizi Wan; Derakhshani, Atefeh; Mofakham, Elmira Banaee; Mallandrich, Mireia; Kumarasamy, Vinoth; Subramaniyan, Vetriselvan (Frontiers in Chemistry, 2024)
Metallic nanoparticles (MNPs) have garnered significant attention due to their ability to improve the therapeutic index of medications by reducing multidrug resistance and effectively delivering therapeutic agents through active targeting. In addition to drug delivery, MNPs have several medical applications, including in vitro and in vivo diagnostics, and they improve the biocompatibility of materials and nutraceuticals. MNPs have several advantages in drug delivery systems and genetic manipulation, such as improved stability and half-life in circulation, passive or active targeting into the desired target selective tissue, and gene manipulation by delivering genetic materials. The main goal of this review is to provide current information on the present issues and prospects of MNPs in drug and gene delivery systems. The current study focused on MNP preparation methods and their characterization by different techniques, their applications to targeted delivery, non-viral vectors in genetic manipulation, and challenges in clinical trial translation.